ARAHAN PENATAAN KAWASAN ULU DAN ILIR TEPIAN SUNGAI MUSI PALEMBANG (KAWASAN AMPERA) DITINJAU DARI KARAKTER FISIK SPASIAL - , Fuji Amalia; , Ir. Slamet Sudibyo, MT. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Musi River separates the city into the region of Palembang Ulu and Ilir connected by Ampera bridges. Both the banks of Ulu and Ilir region of musi river as center of city is area that has a wide variety of activities namely: as public space, residential, commercial, and office buildings. The phenomenon of unequal development of the region between the regions in the area of Ulu and Ilir Ampera has caused of its unity form disharmonious. Therefore its need to considered about how to create a harmony with right arrangement that it becomes a unity of the area whole Ampera region with a strong physical character on the banks of river Musi. This research uses qualitative rationalistic method, approaching with deductive thinking. The research emphasizes on understanding the problems in the field under realistic conditions. Begun by identifying variations of the physical character of the area Ulu and Ilir terms of the spatial physical based on character of elements f the ciry and elements through the water's edge then processing the data result and analyzing it based on theories related. Further conclusions from the analysis of the character of the area Ulu and Ilir Ampera region, then find the determinant elements that reinforces the physical character of the bank area of Ulu and Ilir of the river Musi and the factors affecting the character of it. The results of this research states that there are physical and non physical elements of the determinant of the physical character of the amplifier Ulu and Ilir as a unified whole region Ampera. So that the recommendations directed is the guidelines of Ulu and Ilir arrangement into a unified whole region which has a strong character Ampera waterfront area.